1980
DOI: 10.1056/nejm198012183032503
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Digitalis Therapy Improves Left Ventricular Function in Heart Failure

Abstract: To clarify the controversy regarding the benefits of long-term oral digoxin in the treatment of heart failure, we evaluated hemodynamics at rest and during exercise in nine patients in sinus rhythm with symptomatic heart failure. Patients were studied during long-term digoxin therapy, after withdrawal of the drug, and six hours after readministration. Upon withdrawal of digoxin, pulmonary capillary-wedge pressure increased from 21 +/- 8 to 29 +/- 10 mm Hg, and cardiac index decreased from 2.4 +/- 0.7 to 2.1 +/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
1

Year Published

1984
1984
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 279 publications
(48 citation statements)
references
References 28 publications
0
47
0
1
Order By: Relevance
“…370 The principal adverse reactions occur primarily when digoxin is administered in large doses, but large doses may not be needed to produce clinical benefits. [371][372][373] The major side effects include cardiac arrhythmias (e.g., ectopic and re-entrant cardiac rhythms and heart block), gastrointestinal symptoms (e.g., anorexia, nausea, and vomiting), and neurological complaints (e.g., visual disturbances, disorientation, and confusion). Overt digitalis toxicity is commonly associated with serum digoxin levels greater than 2 ng per mL.…”
Section: Practical Use Of Digitalis In Hf Risks Of Treatmentmentioning
confidence: 99%
“…370 The principal adverse reactions occur primarily when digoxin is administered in large doses, but large doses may not be needed to produce clinical benefits. [371][372][373] The major side effects include cardiac arrhythmias (e.g., ectopic and re-entrant cardiac rhythms and heart block), gastrointestinal symptoms (e.g., anorexia, nausea, and vomiting), and neurological complaints (e.g., visual disturbances, disorientation, and confusion). Overt digitalis toxicity is commonly associated with serum digoxin levels greater than 2 ng per mL.…”
Section: Practical Use Of Digitalis In Hf Risks Of Treatmentmentioning
confidence: 99%
“…Direct measurement of contractility and haemodynamics strongly supports the view that the positive inotropic effect of digoxin is maintained on chronic treatment both in papillary muscles isolated from cats (Williams & Potter 1975) and in man (Arnold et al, 1980;Lee et al, 1982). Murray et al (1982) demonstrated no effect of digoxin in patients at rest but an increased cardiac index and reduced left ventricular pressure on exercise after 6 weeks' treatment.…”
Section: The Problemmentioning
confidence: 73%
“…Digoxin produces immediate and sustained increases in cardiac output and left ventricularejection fraction and decreases cardiac filling pressures in patients with CHF.". 23 Withdrawal of digoxin therapy from patients with CHF leads to symptomatic and functional deterioration. ", ?…”
Section: Digitalismentioning
confidence: 99%